Parent-child mental health in Ukraine in relation to war trauma and drone attacks - Amna Naeem; Iftikhar Sikder; Shanshan Wang; Emily S. Barrett; Nancy Fiedler; Miraj Ahmad; Uyen-Sa D.T. Nguyen; Dmytro Martsenkovskyi; Irina Holovanova; Madelyn Hsiao-Rei Hicks; Ubydul Haque (Comprehensive Psychiatry)
Background: We aimed to address the knowledge gap regarding mental health in Ukrainian children and parents one year after Russia's 2022 full-scale invasion including associations with exposure to drone attacks. Methods: A cross-sectional, quota-sampled survey was conducted among parents of children aged 3–17 in Ukraine one year after the invasion (n = 858). Participants completed self-reported screening measures of the Pediatric Symptom Checklist-17, Child and Adolescent Trauma Screen–Caregiver, Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, the International Trauma Questionnaire, and the University of California, Los Angeles (UCLA) 3-Item Loneliness Scale. We analyzed scores in relation to drone attack exposure using logistic regression. Findings: Many children aged 3–6 years had scores suggestive of ADHD (24.2 %), conduct disorder (20.5 %), and anxiety/mood disorder (12.1 %). Results were similar among children aged 7–17 (anxiety/mood disorder: 24.1 %, conduct disorder: 14.5 %, and ADHD: 14 %). Of the 45.0 % of children aged 3–6 and 57.0 % aged 7–17 exposed to post-invasion trauma, 21.8 % and 17.6 % had clinically relevant levels of PTSD symptoms, respectively. Parental symptoms met screening criteria for depressive disorder in 46.7 % and for anxiety disorder in 24.2 %. All parents reported post-invasion trauma, with 24.5 % screening positive for PTSD. Child mental health disorder odds increased with parental PTSD (OR 1.85, 95 %CI 1.29–2.72) and symptoms meeting screening criteria for depressive disorder (OR 1.99, 95 %CI 1.15–2.56). The odds of children aged 7–17 having clinically relevant levels of PTSD symptoms increased with parental symptoms screening positive for depressive disorder (OR 6.0, 95 %CI 2.0–18.3), anxiety disorder (OR 3.48, 95 %CI 1.76–6.8), and PTSD (OR 3.23, 95 % 1.67–6.2). Parents had a higher prevalence of screening positive for PTSD in high-intensity drone attack regions (28.9 %) than low- and moderate-intensity regions (25.0 % and 20.5 %, respectively, p = 0.04). Interpretation: The high prevalence of children and parents in Ukraine with symptoms screening positive for mental disorders indicates an urgent need for services for school-age children and parents in this war-affected region. High-intensity drone attacks increase the risk of parents screening positive for PTSD.